Changes in coagulation factor XII and its function during aortic arch surgery for acute aortic dissection—a prospective observational study - Li, Jiachen; Guan, Xinliang; Liu, Ou; Wang, Xiaolong; Liu, Yuyong; Li, Haiyang; Lan, Feng; Gong, Ming; Zhang, Hongjia (Journal of Thoracic Disease, 2018)
Background: Changes in the intrinsic coagulation pathway during aortic arch surgery in patients with acute aortic dissection (AAD) have not yet been reported. The aim of this study is to describe the changes in intrinsic coagulation factor XII, explore its function and find a new target for the treatment of coagulopathy during surgery. Methods: Eighty-eight patients undergoing emergent surgery for AAD were enrolled. Changes in the intrinsic and extrinsic coagulation pathways were evaluated at 5 different timepoints during the perioperative period by measuring intrinsic coagulation factor XII, extrinsic coagulation factor VII and some intrinsic upstream stimulating factors. The 88 patients were also divided into two groups according to whether reoperation for coagulopathy was required after surgery. Results: Both coagulation factors XII and VII demonstrated a significant and similar change during the perioperative period. These factors decreased significantly during hypothermia circulation arrest (P